PERAN PARTAI POLITIK (PARPOL) DALAM PENANGGULANGAN KORUPSI - Putu Mantra, I Gede (Institut Hindu Dharma Negeri Denpasar, 2021)
Corruption is a crime against humanity which is classified as an extraordinary crime. The reform movement that took place in 1998 was motivated by public distrust of the ruling government at that time which was thought to be full of collusion, corruption and nepotism (KKN). After the government in power at that time fell, it was followed by a reformation government. One of the agendas of the reform government is the Eradication of Collusion, Corruption and Nepotism (KKN). Various efforts have been made by the government in preventing and eradicating corruption but corruption is still growing. In the midst of rampant corruption committed by public officials, who in fact mostly come from Political Party cadres, it is only natural for political parties (Parpol) to take responsibility and play a role in anti-corruption measures. Through this paper the author tries to look at the factors behind public officials committing acts of corruption, most of which are thought to come from political party cadres (parpol) and see the role of political parties in the prevention and eradication of corruption.From the above discussion, it can be concluded that all efforts and actions through various approaches have been made by law enforcement officials to prevent and eradicate corruption that has been running for years in this country. The responsibility of political parties (parpol) can be started from the recruitment of party cadres before being distributed to various public positions in the government. Political parties are also responsible for cadres who are involved in criminal acts of corruption by not obstructing law enforcers in the investigation and investigation process carried out.Keywords: Political parties, prevention and eradication of corruption.Â